2019
DOI: 10.1002/hep.30814
|View full text |Cite
|
Sign up to set email alerts
|

Vessels Encapsulating Tumor Clusters (VETC) Is a Powerful Predictor of Aggressive Hepatocellular Carcinoma

Abstract: We investigated the clinical significance of a vascular growth pattern of hepatocellular carcinoma (HCC), the vessels that encapsulate tumor clusters (VETC), previously linked to HCC metastatic dissemination. VETC was assessed in a large multi‐institutional cohort of 541 resected HCCs from Italy, Korea and Japan, and matched against a full spectrum of clinical and pathological variables. The VETC phenotype (defined as ≥ 55% tumor area by CD34 immunostaining) was easily reproducible and reliably detectable in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(226 citation statements)
references
References 17 publications
13
192
3
Order By: Relevance
“…VETC is a peculiar vascular phenotype, originally described by Fang et al[45]. We recently confirmed its strong impact on the prognosis of resectable HCC[46]. Moreover we observed the close correlation of VETC with several ominous prognostic features such as MVI.…”
Section: Pathological Diagnosis Of Hcc and Prognostic Markerssupporting
confidence: 84%
See 1 more Smart Citation
“…VETC is a peculiar vascular phenotype, originally described by Fang et al[45]. We recently confirmed its strong impact on the prognosis of resectable HCC[46]. Moreover we observed the close correlation of VETC with several ominous prognostic features such as MVI.…”
Section: Pathological Diagnosis Of Hcc and Prognostic Markerssupporting
confidence: 84%
“…In the first group, HCC presents as well-differentiated tumors with cholestasis and microtrabecular and pseudoglandular patterns of growth; in the second, HCC is mostly poorly differentiated with frequent vascular invasion. Using the corresponding im-munohistochemical markers (p53, β-catenin, and GS) we have recently confirmed the clinical-pathological correlations of these two subclasses in the daily clinical practice[46]; however, none of these categories proved to be of prognostic relevance[31,48]. Interestingly, the subgroup of HCC correlated to β-catenin pathway activation was recently associated with an exhausted immune infiltrate[49].…”
Section: Pathological Diagnosis Of Hcc and Prognostic Markersmentioning
confidence: 94%
“…They suggested that this vascular pattern was an effective mode of HCC metastasis independent of epithelial-to-mesenchymal transition. In 2019, Renne et al demonstrated that it was an independent risk factor for early recurrence and decreased overall survival in a large multi-institutional cohort containing 541 resected HCCs from Italy, South Korea, and Japan (73). Seemingly, it reminds us that the MVD influence the clinical outcomes of HCC, and the heterogeneity of vascular patterns might regulate HCC progression.…”
Section: Vascular Patterns That Influence Mvdmentioning
confidence: 99%
“…This special microvascular pattern, which ranges from 18.9 to 45.2% in HCC (70,71,73), ordinarily has a lower blood vessel density than ordinary capillary-like pattern and tends to form a large vessel lumen (76). Importantly, it has independent negative effects on OS and DFS (69)(70)(71)(72)(73). Neglecting the possible impacts of microvascular pattern on prognosis will cause unpredictable interference for the judgment of the actual role of MVD.…”
Section: Prognostic Value Of Mvd In Hccmentioning
confidence: 99%
“…The main histological determinant for a high recurrence risk is the presence of microvascular invasion (MVI) [6]. In addition, a novel parameter might be the vessel encapsulating tumor cluster, which is also associated with a higher recurrence rate after surgical therapy [7]. Since both features are difficult or even impossible to assess on preoperative biopsies, these biological parameters are not included in the preoperative treatment planning for HCC.…”
Section: Primary Liver Tumorsmentioning
confidence: 99%